Conceptual Metaphors in Different Types of Discourse - Brazienė, Veronika (Respectus Philologicus, 2004)
The subject matter of the present article is an overview of the theory of conceptual metaphor and the application of this theory to different types of discourse. The theory of conceptual metaphor is presented mostly from the point of view of George Lakoff and his co-author Mark Johnson. Discourse analysis is rendered within the framework of the theory developed by Jacques Derrida following its account in the monograph of Eleonora Lassan "Discourse of Power and Dissidence in the USSR" and an article "Metaphorisation and Discourse" by N. Belozerova. Practical application of the theories is illustrated by the examples of political and propagandistic discourse. The Address to the Nation of the US President George Bush of 19 March 2003 delivered at an early stage of the US war against Iraq serves as an illustration of political discourse. Propagandistic posters of the Soviet era, starting with the post-revolutionary period and finishing with the period of "cold war" and the acme of struggle against the "world imperialism" illustrate the application of conceptual metaphor theory to propagandistic discourse.